2019
DOI: 10.1038/s41467-019-10596-0
|View full text |Cite
|
Sign up to set email alerts
|

Developmental kinetics and transcriptome dynamics of stem cell specification in the spermatogenic lineage

Abstract: Continuity, robustness, and regeneration of cell lineages relies on stem cell pools that are established during development. For the mammalian spermatogenic lineage, a foundational spermatogonial stem cell (SSC) pool arises from prospermatogonial precursors during neonatal life via mechanisms that remain undefined. Here, we mapped the kinetics of this process in vivo using a multi-transgenic reporter mouse model, in silico with single-cell RNA sequencing, and functionally with transplantation analyses to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 76 publications
5
98
0
Order By: Relevance
“…Because we characterized translation and DAZL’s targets in undifferentiated spermatogonia from a synchronized first round of spermatogenesis, some of our results may represent the unique regulation that occurs within the first round, which originates from prospermatogonia, as opposed to later cycles of spermatogenesis, which arise from spermatogonial stem cells derived from prospermatogonia ( Hermann et al, 2015 ; Law et al, 2019 ; Yoshida et al, 2006 ). Our data may also reflect the larger spermatogonial stem cell pool that is established in the neonatal testis during synchronization ( Agrimson et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because we characterized translation and DAZL’s targets in undifferentiated spermatogonia from a synchronized first round of spermatogenesis, some of our results may represent the unique regulation that occurs within the first round, which originates from prospermatogonia, as opposed to later cycles of spermatogenesis, which arise from spermatogonial stem cells derived from prospermatogonia ( Hermann et al, 2015 ; Law et al, 2019 ; Yoshida et al, 2006 ). Our data may also reflect the larger spermatogonial stem cell pool that is established in the neonatal testis during synchronization ( Agrimson et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the paucity of available data on perinatal human male germline development, the exact in vivo stage to which T1LCs correspond remains unclear. Recent studies have suggested that SSC activity, or the competency to produce self-sustaining spermatogenesis upon transplantation, has already been established, at least in part, in fetal prospermatogonia in mice 49 . It is therefore possible that T1LCs might be close to foundational SSCs, which upon transplantation, would be capable of regenerating complete spermatogenesis.…”
Section: Hoxb4 Hoxb2 Hoxa5 Hoxb8 Hoxb5 Six1 Hoxb6mentioning
confidence: 99%
“…In the postnatal mouse testis, prospermatogonia give rise to spermatogonia, exhausting the prospermatogonia population by postnatal day 5 (P5) ( Drumond et al., 2011 ; Kluin et al., 1982 ; Yoshida et al., 2006 ). By P6-8, distinct spermatogonial subtypes (SSC, progenitor, differentiating) can be distinguished on the basis of specific marker proteins ( Buaas et al., 2004 ; Chan et al., 2014 ; Valli et al., 2014 ), lineage tracing ( Hara et al., 2014 ; Sun et al., 2015 ), bulk ( Helsel et al., 2017 ), and single-cell (sc) ( Chen et al., 2018 ; Ernst et al., 2019 ; Green et al., 2018 ; Grive et al., 2019 ; Guo et al., 2018 ; Hermann et al., 2018 ; Jung et al., 2019 ; Law et al., 2019 ; Liao et al., 2019 ; Sohni et al., 2019 ; Velte et al., 2019 ) RNA-sequencing (RNA-seq), or transplantation analysis ( McLaren, 2003 ; Shinohara et al., 2000 ). SSCs retain regenerative capacity and divide to either self-renew or generate progenitors that lose regenerative capacity as they become primed to initiate spermatogenic differentiation giving rise to differentiating spermatogonia ( Drumond et al., 2011 ; Kluin et al., 1982 ; Yang et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%